Neuronal ceroid lipofuscinosis and arthropathy: a family study. Issue 2 (April 1981) - Proops, R; Green, S H
Abstract : A family is described in which three children have neuronal ceroid lipofuscinosis and two of them also have an arthropathy. Clinically the children have the late infantile form but pathological evidence shows the recognised overlap with the juvenile form. A fourth child with joint involvement but with normal skin biopsies is described. It is suggested that this family have a specific form of neuronal ceroid lipofuscinosis with arthropathy and that accumulation of metabolites in this storage disease may be age dependent.